A spatial graph model for managing service networks in geographical information systems - Montilva, Jonás (Rev. Téc. Fac. Ing. Univ. Zulia)
Representing, manipulating and visualizing service networks in geographical information systems have been usually performed through vector-based and raster spatial data models. These models have limited semantic expressiveness for modeling service networks. The spatial properties of the entities (nodes and arcs/ edges) of a network are simplified by a geometric graph made of points and lines. On the other hand, the non spatial properties of a network are managed separately from the spatial properties, which forces the user to become familiar with two different modeling notations. This paper introduces an object model for representing, manipulating and visualizing service networks in 2D and 3D. The model is based on the notion of spatial graph, which emerged from the integration of geometric graphs and spatial objects. The distinguished feature of the model is its ability to capture the geometrical and topological properties of a service network and express them in a direct, natural and simple manner.